Evolution of the amorphous structure in melt-spun Ti50Ni25Cu25 alloy subjected to high pressure torsion deformation. (November 2015) - Gunderov, D.V.; Slesarenko, V.Yu.; Churakova, A.A.; Lukyanov, А.V.; Soshnikova, E.P.; Pushin, V.G.; Valiev, R.Z.
Abstract: Peculiarities of structure and mechanical behaviour of amorphous Ti50 Ni25 Cu25 alloy were the focus of this research. The melt-spun ribbons of amorphous Ti50 Ni25 Cu25 were subjected to high pressure torsion (HPT) at temperatures of 20–150 °C in order to modify their structure and mechanical behaviour. Some features of obtained HPT-processed samples were compared with initial state with the help of x-ray diffraction (XRD), transmission electron microscopy (TEM) and nanohardness testing. Analysis of structural data and mechanical behaviour allowed us to assume that severe plastic deformation (SPD) processing of melt-spun Ti50 Ni25 Cu25 alloy might lead to the formation of the structure similar to the new kind of noncrystalline state – "nanoglass" state. Highlights: High pressure torsion leads to the modification of initial amorphous structure. Young modulus increase after high pressure torsion. Microstructure of produced alloys depends on the processing temperature.